Canada : Financial Sector Assessment Program-Technical Note-Deposit-taking Sector: Regulation and Supervision. (IMF Staff Country Reports; Country Report ;, 2020)
The Technical Note focuses on sizeable mortgage exposures and persistent housing market imbalances. The review evaluated oversight of deposit-taking institutions (DTIs) in federal jurisdiction, as well as in British Columbia and Quebec. There are many good, well-functioning mechanisms in place for cooperation. Areas that warrant improvement about DTI regulation and supervision include policy development, especially between Office of the Superintendent of Financial Institutions (OSFI) and Autorite des marches financiers, coordination of data collection, and exchange of useful prudential information between different agencies. The authorities should explore how to remove barriers that prevent close and meaningful cooperation. Risk weights on mortgage lending appear too low for insured mortgages and may not be sufficiently through-the-cycle for banks using the Internal Ratings Based approach. A common forbearance definition and monitoring framework for credit risk (in the context of loan restructuring by DTIs should be adopted across all jurisdictions in Canada. A similar definition, in line with the guidance of the Basel Committee for Banking Supervision, and consistent data will help improve risk monitoring especially given the importance of debt restructuring for managing problem real estate exposures. Finally, OSFI's guideline on asset pledging should ensure enough unencumbered assets to support the claim of depositors.